Implementation and application of automata : 20th International Conference, CIAA 2015, Umeå, Sweden, August 18-21, 2015 : proceedings /: 20th International Conference, CIAA 2015, Umeå, Sweden, August 18-21, 2015 : proceedings. ([2015]) - Unknown
No abstract available